Conteúdos Matemáticos da Educação Básica e sua abordagem em cursos de Licenciatura em Matemática - Santos, Roberto Cavalcante dos (2005)
This thesis is devoted to the study of ifMathematics in the curriculum structure and teachers formationli, included in the Postgraduate Course Studies of the Mathematics Education Program at PUC/SP and is part of the ihFormation of Mathematics Teacherslc Research Project, which gathers a set of investigations that study the processes of initial and continuous formation of Mathematics Teachers in Undergraduate courses and in projects of continuous formation, aiming at identifying changes that have already been implemented, given the current demands of the Brazilian educational system. The focus of this study is to investigate what has been done in regard to the Mathematics curriculum of Elementary Education and how course coordinators understand the articulations between Mathematics curricula learned in Undergraduate courses and the school curriculum programs that will be taught by future teachers. It also investigates where graduate students who have majored in Mathematics stand, as far as their own formation to teach Mathematics is concerned. To carry out this study, we have analyzed other works done in the area of Mathematics teaching related to Undergraduate Mathematics programs, in addition to the local education law in practice. We have also looked into on line school curricula and syllabuses of some leading education institutions, as well as surveys conducted with Mathematics course coordinators and the opinion of last year Mathematics majors on how they see their own education. The results show that it is extremely hard to discuss the approach on the Elementary Education curricula, which future teachers are going to teach, without reviewing contents, in order to set the requirements of the other subjects in the Undergraduate program and by justifying this with the low performance in Mathematics of the students who enroll in Math school. In their turn, the surveyed students show a great concern with their own ability to teach basic contents. We hope this work can contribute to the discussion of alternative proposals regarding the initial formation of Mathematics teachers